2007
DOI: 10.1136/hrt.2003.025270
|View full text |Cite
|
Sign up to set email alerts
|

Clinical epidemiology of heart failure

Abstract: The aim of this paper is to review the clinical epidemiology of heart failure. The last paper comprehensively addressing the epidemiology of heart failure in Heart appeared in 2000. Despite an increase in manuscripts describing epidemiological aspects of heart failure since the 1990s, additional information is still needed, as indicated by various editorials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
1,138
1
117

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,660 publications
(1,280 citation statements)
references
References 26 publications
24
1,138
1
117
Order By: Relevance
“…People with HF often experience a reduction in quality of life, higher mortality rates, and increased risk for other CVD events 31, 32, 33, 34. More than half of the people diagnosed with HF will die within 5 years 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…People with HF often experience a reduction in quality of life, higher mortality rates, and increased risk for other CVD events 31, 32, 33, 34. More than half of the people diagnosed with HF will die within 5 years 32, 33.…”
Section: Discussionmentioning
confidence: 99%
“…Heart failure (HF) is a relatively common condition, occurring in 1% to 2% of the adult population in Western countries 1, 2. There are a number of factors contributing to ongoing and projected increases in the prevalence of HF, including the aging population demographic and improved patient survival 3, 4.…”
Section: Introductionmentioning
confidence: 99%
“…Prior epidemiological studies have identified a number of important prognostic factors associated with poor long‐term outcomes for patients with ADHF including advanced age, male sex, hyponatremia, lower systolic blood pressure, poorer kidney function, and several comorbid conditions 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. Many of these earlier studies examined the role of various prognostic factors in patients with HF that had not further been stratified according to EF findings, and among those that did,11, 13, 14, 15, 16, 17 none used the 2013 AHA/ACC guidelines recommending specific EF cut points 2.…”
Section: Introductionmentioning
confidence: 99%